Assessing HIV/AIDS knowledge and stigmatizing attitudes among medical students in Universiti Putra Malaysia - Chew, Boon How; Cheong, Ai Theng (Malaysian Medical Association, 2013)
OBJECTIVE: Medical students are future doctors who are trained to treat all kind of diseases including people living with HIV/AIDS (PLWHA) without prejudice. This study was to determine the factors associated with knowledge on HIV/AIDS and stigma towards PLWHA among medical students. METHODS: This was a cross sectional study with stratified random sampling conducted in a public university, Malaysia. The participants were preclinical-year (year 1 and year 2) and clinical-year (year 3 and year 4) medical students. Simple randomisation was carried out after stratification of medical students into preclinical and clinical-year. The selfadministered questionnaires were consisted of sociodemographic data, items assessing HIV/AIDS knowledge and items assessing stigmatisation attitudes towards PLWHA. RESULTS: We had 100% response rate of 340 participants. Pre-clinical and clinical year medical students each contributed 170 (50%). Majority was female (64.1%). About two-thirds (60.6%) was Malay, followed by Chinese (31.2%) and Indian (7.1%). Pre-clinical students were significantly more stigmatizing in subscale of "attitudes towards imposed measures" (t=3.917, p<0.001), even with adjustment for previous encounter and ethnicity (B= 1.2, 95% CI 0.48 to 1.83, p=0.001). On the other hand, clinical students were found to be significantly less comfortable in handling HIV/AIDS cases (t=0.039, p=0.039), even after controlled for previous encounter and ethnicity (B=0.6, 95% CI 0.29 to 0.98, p< 0.001). CONCLUSION: Clinical encounter with PLWHA was associated with higher knowledge in HIV/AIDS. Medical students in preclinical years were having stigmatizing attitude towards imposed measures compared to the clinical years who had more stigmatizing attitude in being less comfortable with PLWHA.